THE USE, ABUSE AND MISUSE OF HUMAN RIGHTS: CHALLENGES AND PROSPECTS - Andreopoulos, George (REVISTA ESMAT, 2021)
The concept of human rights has confronted a series of challenges over the years. Yet, the concept has retained considerable appeal, an appeal that is reflected in the various ways in which the concept has been, and continues to be, used, abused and misused. This article is divided into two sections: the first section defines and discusses the key terms of use, abuse and misuse; the second section briefly addresses two of the major challenges currently facing human rights: (1) the responses to transnational terrorism on the aftermath of the 9/11 attacks; and (2) the proliferation of states of emergency during the COVID-19 pandemic.